Pendampingan Baca Tulis Qur’an (BTQ) Anak TPQ Di Desa Kebonrejo Kecamatan Kepung - Ahmad Fadli Rosyad; Miftakhul Arif (LP3M IAIFA Kediri, 2021)
The recent social environment is widely coloured by anarchist actions, the loss of Islamic values and so on. The program is focused on fostering Quranic writing and reading skills for school-age children. This skill in writing and reading the Qur'an is expected in how to write short letters in the Qur'an in accordance with the rules of good and true Arabic writing and how to read the Good and True Qur'an. This program has sustainability with TPQ programs located in Kebonrejo village of Kediri District. The santri who had not memorized and knew about the science of tajwid and makhroj within a month were able to master the science of tajwid by reading quite well and writing, especially with good and true lafad-lafad alQur'an. Evident from the 10 children who studied this BTQ program 3 children among them champion one two and three in TPQ Nuril Huda Kebonrejo, Kepung, Kediri.